2021
DOI: 10.3390/plants10102035
|View full text |Cite
|
Sign up to set email alerts
|

Response of Three Miscanthus × giganteus Cultivars to Toxic Elements Stress: Part 1, Plant Defence Mechanisms

Abstract: Miscanthus × giganteus demonstrated good phytostabilization potentials in toxic element (TE) contaminated soils. However, information about its tolerance to elevated concentrations is still scarce. Therefore, an ex-situ pot experiment was launched using three cultivars (termed B, U, and A) grown in soils with a gradient Cd, Pb and Zn concentrations. Control plants were also cultivated in non-contaminated soil. Results show that the number of tillers per plant, stem diameter as well as leaf photosynthetic pigme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 42 publications
1
10
2
Order By: Relevance
“…Table 1 represents the TE concentrations in the studied soils. As previously shown by Al Souki et al [ 20 , 24 ], the TE concentrations in MC were in agreement with the regional background values (0.42, 38, and 74 mg kg −1 , corresponding to Cd, Pb, and Zn, respectively). Whereas the other soils displayed pseudo total concentrations 20 to 50 times higher than the regional agricultural background values.…”
Section: Methodssupporting
confidence: 90%
See 4 more Smart Citations
“…Table 1 represents the TE concentrations in the studied soils. As previously shown by Al Souki et al [ 20 , 24 ], the TE concentrations in MC were in agreement with the regional background values (0.42, 38, and 74 mg kg −1 , corresponding to Cd, Pb, and Zn, respectively). Whereas the other soils displayed pseudo total concentrations 20 to 50 times higher than the regional agricultural background values.…”
Section: Methodssupporting
confidence: 90%
“…However, the experiments that evaluate TE impacts on miscanthus health are scarce and have never been undertaken for more than three months. In the previous work [ 24 ], after a full growing cycle on TE contaminated soils (T1), we demonstrated that miscanthus plants exhibited TE-induced stress (an increase in antioxidant enzymatic activities, a decrease in photosynthetic pigment content, and an enhancement of secondary metabolite accumulation). However, results also demonstrated that miscanthus plants were quite tolerant to TEs as no significant differences were observed between plants growing on different soils with an increasing gradient in TE concentrations.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations